1998
DOI: 10.1007/s005350050150
|View full text |Cite
|
Sign up to set email alerts
|

A new quadruple therapy for the eradication of Helicobacter pylori . Effect of pretreatment with omeprazole on the cure rate

Abstract: To elucidate whether pretreatment with omeprazole decreases the cure rate of Helicobacter pylori infection with a new quadruple therapy, and thus, whether this pretreatment should not be used in clinical practice, we conducted a randomized trial. Ninety patients with chronic peptic ulcer disease and nonulcer dyspepsia, with biopsy-proven H. pylori infection were randomly assigned to the two following regimens: Group 1 (n = 45) received omeprazole 20 mg once daily for 2 weeks (days 1-14), and 500 mg amoxicillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…The authors theorized that PPIs might induce coccoid-persistent forms of H. pylori in a direct or indirect manner and that H. pylori exposed to PPIs were in a less active, dormant state and therefore less vulnerable to the actions of antibiotics. Other studies have reported that pretreatment with a PPI did not reduce the rate of eradication [5,6,7,17]. Janssen et al [8] have reported the results of a meta-analysis indicating that pretreatment did not influence eradication, but this meta-analysis did not include the regimen recommended in Japan (lansoprazole, amoxicillin and clarithromycin).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors theorized that PPIs might induce coccoid-persistent forms of H. pylori in a direct or indirect manner and that H. pylori exposed to PPIs were in a less active, dormant state and therefore less vulnerable to the actions of antibiotics. Other studies have reported that pretreatment with a PPI did not reduce the rate of eradication [5,6,7,17]. Janssen et al [8] have reported the results of a meta-analysis indicating that pretreatment did not influence eradication, but this meta-analysis did not include the regimen recommended in Japan (lansoprazole, amoxicillin and clarithromycin).…”
Section: Discussionmentioning
confidence: 98%
“…However, it was subsequently reported that initial treatment with a proton pump inhibitor (PPI), either with triple therapy (pantoprazole, clarithromycin and metronidazole; or omeprazole, amoxicillin and metronidazole) or with quadruple therapy (omeprazole, amoxicillin, metronidazole and roxithromycin) did not reduce the H. pylori eradication rate [5,6,7]. Furthermore, based on a meta-analysis, Janssen et al reported that pretreatment with a PPI did not influence H. pylori eradication [8].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of all four drugs (the PPI, clarithromycin, metronidazole/ tinidazole, and amoxicillin being given b.i.d.. The duration has ranged from 3 to 7 days and it has resulted in Grade B results similar to those obtained with sequential therapy [59][60][61][62][63][64][65][66][67] ( Figure 3). As with sequential therapy, studies are needed to test whether extending the duration of therapy will improve the results.…”
Section: Treatment Recommendations For Initial Treatmentmentioning
confidence: 99%
“…From reference 14 , with permission. Weight mean and 95% confidence intervals for 16 studies of sequential therapy (n = 1805) for 10 days(modified intention-to-treat) 57 and 9 studies of concomitant therapy (n = 715) ranging from 3 to 7 days (intention-to-treat) [59][60][61][62][63][64][65][66][67] .…”
Section: Key Pointsmentioning
confidence: 99%
“…The superiority of this therapy over standard triple therapy has been widely documented (7). Meanwhile, concomitant therapy, first introduced in 1998 (8,9), is now being reconsidered as a firstline H. pylori eradication therapy (10). The concomitant regimen includes quadruple therapy with standard triple therapy (PPI, clarithromycin, amoxicillin) plus metronidazole or tinidazole.…”
Section: Introductionmentioning
confidence: 99%